Perancangan Media Pembelajaran pada Mata Kuliah Jaringan Nirkabel di Prodi PTIK IAIN Bukittinggi Berbasis Augmented Reality - Vikri, Muhammad; Efriyanti, Liza; Supriadi, Supriadi; Okra, Riri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This research was carried out from the problems that have been observed by the authors at IAINBukittinggi which were found, where students were constrained in understanding the material because the wireless network material requires a lot of tools and materials so that it requires a lot of money, and the tools available in the laboratory are still lacking and there are tools that are needed. damaged where this has an impact on the understanding of the material that is still lacking in students about wireless networks. Therefore, the authors design learning media based on augmented reality with the aim of beinga medium that can support learning in order to help improve student understanding, and attract student interest in learning. The purpose of this research is to produce a design for supporting learning media for wireless networks based on augmented reality that is valid, practical and effective. The method used in this study is a research and development (R&D) method using the Luther-Sutopo version of the multimedia development life cycle (MDLC), which consists of six stages, namely concept (conception),design (design), collecting material (material collection). ), assembly (manufacture), testing (testing) and distribution (distribution). There are three product tests conducted in this study, namely validity test, practicality test and effectiveness test. Based on the product test results that have been carried out by theauthor of the validity test, the average value is 0.91 which is declared valid, and for the practicality test, the average value is 0.67 which is declared practical and for the effectiveness test, the average value is obtained. the average is 0.90 which is declared effective.